2013
DOI: 10.5455/2320-6012.ijrms20130206
|View full text |Cite
|
Sign up to set email alerts
|

A study of neonatal and maternal outcomes of asthma during pregnancy

Abstract: INTRODUCTIONAsthma is a common problem around the world with variable prevalence ranging from 1%-18% 1 in different age and geographical distribution. There are proximately 300 million affected individuals in the world. Study by Kwon HL et al suggests that approximately 4.1% of all pregnant women had experienced an asthma attack in previous year.2 Recent study in USA suggests 3.7-8.4% of women had asthma in 1997-2001, as compared to 3.2% according to data in 1988-1994. 3 There are growing prevalence and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
3
4
0
Order By: Relevance
“…Another study done by Gustaf Rejno et al had a significant association between maternal asthma and emergency cesarean section (adj OR 1.29;95% CI 1.23-1.34) [14]. In our study we found that 11(10.1%) of asthmatic women and 9(8.3%) non asthma had antepartum haemorrhage which is consistent with finding of Meena BL et al [15]. The effect of asthma exacerbations on reduced fetal growth is independent of any changes in gestational age at delivery.…”
Section: Discussionsupporting
confidence: 82%
“…Another study done by Gustaf Rejno et al had a significant association between maternal asthma and emergency cesarean section (adj OR 1.29;95% CI 1.23-1.34) [14]. In our study we found that 11(10.1%) of asthmatic women and 9(8.3%) non asthma had antepartum haemorrhage which is consistent with finding of Meena BL et al [15]. The effect of asthma exacerbations on reduced fetal growth is independent of any changes in gestational age at delivery.…”
Section: Discussionsupporting
confidence: 82%
“…The results showed that the prevalence of asthma in pregnant women living in the Sabzevar region was 2.1%. That is similar to the prevalence in India, according to Meena's study (14). In a 2007 study, Karimi et al identified circa 5.6% of pregnant women as being asthmatic (12).…”
Section: Discussionsupporting
confidence: 67%
“…There was also an increased incidence of caesarean delivery in asthmatic women. One possible reason for this is that pregnant asthmatics are considered high-risk patients, and so are more likely to undergo surgery, as compared to healthy pregnant women [ 33 ]. In this study [ 33 ], caesarean was performed in 52.9 and 34.2% of asthmatics and non-asthmatics, respectively, in close agreement with our results of 52.9 and 33.0%.…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason for this is that pregnant asthmatics are considered high-risk patients, and so are more likely to undergo surgery, as compared to healthy pregnant women [ 33 ]. In this study [ 33 ], caesarean was performed in 52.9 and 34.2% of asthmatics and non-asthmatics, respectively, in close agreement with our results of 52.9 and 33.0%. Our results are also comparable to those of Dombrowski et al [ 34 ], where the highest rate of caesarean sections occurred in cases of intermittent and mild persistent asthmatics, at the rates of 53.8 and 70.0%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation